Análise da influência de um parque eólico no escoamento médio atmosférico na região do pampa gaúcho - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The main objective of this work is to analyze the influence of a wind farm on the variables that control the atmospheric flow in the atmospheric boundary layer (ABL). The period simulated was the whole year of 2008, by using two different configurations: without wind farm (simply Weather Research and Forecasting (WRF) model) and with a wind farm (the WRF model with the module Fitch, which parameterizes the influence of the wind turbines in the atmospheric flow), both of them using the boundary layer module (PBL-module) Yonsei-University (YSU). From the simulations without the wind farm the model validation is done, with the observed data collected in two automatic stations of Instituto Nacional de Meteorologia (INMET), in Alegrete-RS e Quaraí-RS. The correlation ratio for the stations of Alegrete-RS and Quarai-Rs was, approximately, 80% a 85%, respectively. However, this analysis, also showed a tendency in the model overestimation of the observed data. The idealized wind farm, in this work, has 100 wind turbines of 3 MW of power with 120 m of height and with rotor measuring 125 m of diameter. The results show that the wind farm would generate, in 2008, 89; 1 MWh of electric energy, with a capacity factor of 29; 7%. From the comparison between the results of the simulations with both configurations, the influence of the presence of the wind farm over the behavior of the variables that control the mean flow in the atmosphere is analyzed. In spite of adequate answer of the wind velocity, the temperature and the turbulence of the flow decreases in the presence of the wind farm, although the parametrization for the wind turbines to change part of the mechanical energy of the flow part in heat and in part in turbulence. An analysis of the dependence of the turbulence, near the ground, with the vertical stability of the flow indicates that the turbulence generate by turbines does not arrive in the low levels of the atmosphere. This problem can be directly caused by the PBL-module chosen.
Keywords: Engenharia; Energias renováveis; Usina eólica; Pampa gaúcho; Turbulência; Modelagem atmosférica; Engineering; Renewable energy; Wind farm; Turbulence; Atmospheric modeling; CNPQ::ENGENHARIAS